Value Creation and Stock Price Dynamics in the Construction Sector: An Indonesian Perspective: Penciptaan Nilai dan Dinamika Harga Saham dalam Sektor Konstruksi: Perspektif Indonesia - Yulva Maulit Diana; Sriyono Sriyono (Academia Open, 2022)
This study investigates the impact of Economic Value Added (EVA), Market Value Added (MVA), Financial Value Added (FVA), and Return on Investment (ROI) on stock prices in the Indonesian construction industry from 2014 to 2018. A purposive sampling technique was employed, resulting in a sample size of 12 companies. Using multiple linear regression analysis, the study explores the relationships between EVA, MVA, FVA, ROI as independent variables, and stock prices as the dependent variable. The findings reveal that EVA exerts a significant negative influence on stock prices, while MVA and FVA exhibit a significant positive effect. However, no significant relationship was observed between ROI and stock prices. These results contribute to a better understanding of the value creation mechanisms in the construction industry, offering valuable insights for investors, practitioners, and policymakers in optimizing investment decisions and fostering sustainable growth. Highlights: Value Creation in Construction: This study explores the impact of Economic Value Added (EVA), Market Value Added (MVA), and Financial Value Added (FVA) on stock prices in the Indonesian construction industry. Contrasting Effects: The findings reveal a significant negative relationship between Economic Value Added (EVA) and stock prices, while Market Value Added (MVA) and Financial Value Added (FVA) exhibit a significant positive influence. Return on Investment (ROI): Surprisingly, the study finds no significant impact of Return on Investment (ROI) on stock prices in the construction companies analyzed, highlighting the need for further investigation into value drivers in this sector. Keywords: Value creation, Stock prices, Construction sector, Economic Value Added (EVA), Market Value Added (MVA)